1982
DOI: 10.1136/bmj.284.6315.539
|View full text |Cite
|
Sign up to set email alerts
|

Sodium-potassium cotransport activity as genetic marker in essential hypertension.

Abstract: 539hypertensive action of ketanserin is thus characterised by a favourable haemodynamic profile. The observation that ketanserin lowered not only systemic arterial pressure but also cardiac filling pressures suggests that this balanced vasodilatation may be of particular interest for the treatment of congestive heart failure. Indeed, a favourable response to ketanserin in this condition has been reported recently."' 5-HT not only acts as a direct vasoconstrictor, but it also amplifies the vasoconstrictor respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

1983
1983
2003
2003

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…At present, a lack of agreement exists in regard to this possibility (38)(39)(40). Therefore, it seems reasonable to conclude that the difference in erythrocyte Na+ concentration between blacks and whites is at least partially a result of a variation in the Na+-K+-ATPase activity, while a contribution of the Na+,K+-cotransport system to this difference may also exist.…”
Section: Discussionmentioning
confidence: 78%
“…At present, a lack of agreement exists in regard to this possibility (38)(39)(40). Therefore, it seems reasonable to conclude that the difference in erythrocyte Na+ concentration between blacks and whites is at least partially a result of a variation in the Na+-K+-ATPase activity, while a contribution of the Na+,K+-cotransport system to this difference may also exist.…”
Section: Discussionmentioning
confidence: 78%
“…17 Davidson et al 18 did not confirm these observations in the South African population, noting no differences for blacks and whites, although within each race, hypertensives tended to be lower than normotensives. Canessa et al 19 have suggested in a preliminary report that hypertension is associated with lower cotransport activity in American blacks but not in whites.…”
mentioning
confidence: 65%
“…Cotransport values were virtually absent to very low in all hypertensive subjects sampled from this population, which has a very high incidence of hypertension. In a study from Capetown, South Africa, Davidson et al 12 reported lower levels of RBC cotransport expressed as the mean value of Na + plus K + efflux in black, Caucasian, and racially mixed hypertensive patients compared to normotensive subjects. They did note a large overlap of values among study groups and could not detect an environmental influence on RBC cotransport activity.…”
Section: Discussionmentioning
confidence: 99%
“…One other study noted no differences in RBC cotransport between untreated and hypertensive patients treated with various antihypertensive agents. 12 It is uncertain whether that study examined prospectively in the same patients the effects of blood pressure reduction on RBC cotransport before and during therapy. Erythrocyte Na+,K+ cotransport and Na+,K+ pump in black and caucasian…”
Section: Discussionmentioning
confidence: 99%